Li-NMC batteries model evaluation with experimental data for electric vehicle application - Baczynska, Aleksandra (2018)
The aim of the paper is to present the battery equivalent circuit for electric vehicle application. Moreover, the model described below is dedicated to lithium-ion types of batteries. The purpose of this paper is to introduce an efficient and transparent method to develop a battery equivalent circuit model. Battery modeling requires, depending on the chosen method, either significant calculations or a highly developed mathematical model for optimization. The model is evaluated in comparison to the real data measurements, to present the performance of the method. Battery measurements based on charge/discharge tests at a fixed C-rate are presented to show the relation of the output voltage profiles with the battery state of charge. The pulse discharge test is presented to obtain the electric parameters of the battery equivalent circuit model, using a Thevenin circuit. According to the Reverse Trike Ecologic Electric Vehicle (VEECO RT) characteristics used as a case study in this work, new values for vehicle autonomy and battery pack volume based on lithium nickel manganese cobalt oxide cells are evaluated.